Houses as collective processes. Ethnographic reflections on the political practices of women in the popular economy - Pacífico, Florencia Daniela (Revista de Antropologia, 2022)
In this article, I propose an ethnographic analysis of the connections between houses construction and material reform processes and a set of collective political practices carried out by women from popular sectors in relation with the implementation of state programs and the action of social organizations. I show that the development of collective practices influences houses, while their materiality and the possibility of transforming them, can constitute a relevant base to build modalities of political organization and forms of militancy. Trying to contribute to a broader reflection on the limits of what we define as political and taking distance from dual gazes, I argue that houses can be thought of as collective political processes from where issues commonly defined as part of "private" or "domestic" life are politicized.